Local governance under austerity: hybrid organisations and hybrid officers. (27th July 2018) - Pill, Madeleine; Guarneros-Meza, Valeria
Abstract : Using the case of Cardiff, Wales, we argue that the hybridisation of local governance forms is exacerbated by the downscaling and offloading of austerity politics. Conceptualising hybridity as a process which operates across governmental scales, at the organisational and at the individual level helps understand the growing complexities of local governance under austerity and the tensions which arise in seeking to assemble locally appropriate ideas and practices. Conceptualising hybridity as practice, we consider how 'hybrid officers' at the frontline experience austerity, their situated agency, and the implications for higher levels of governance.